EVALUATION AND DESIGN REPAIRMENT TO INCREASE DRYING CAPACITY ON DRIED SNACK DRYING MACHINE - FIKRI RAMADHANA (NIM : 13106050); Dosen Pembimbing : Dr. Ir. Abdurrachim Halim, MUHAMMAD
This final project contained analysysÃ‚Â’ about performance of conveyor dryer which operated at PT. Tanindo Prima Multi. The conveyor dryer used to dry dried snack. To fulfill their production target, PT. Tanindo Prima Multi used two ways of drying, using solar heat and using the conveyor dryers. The conveyor dryers operated each day for 8 hours and able to produce about 1600 kg of dried product per day. But, the company would face production problem if the weather is not allow to use solar heat to dry the product. To anticipate this problem, increase in the dryer production capacity is necessary. The conveyor dryer performance analysis is based on two parameters, the heat transfer rate of heat exchanger which applied on the dryer, and the drying capacity of the air supplied to the dryer. After the analysis about the dryer current performance is finished, several changes in the dryer design are designed. The design changes are on the air inlet ductline, adding pre-heater into the air heating system, and adding screen to create plenums at each air inlet. From those several design changes, the result shows that the heat transfer rate would increase from about 20-30 kW for each heat exchanger, to about 120 kW. The pre-heaters added in the new design are predicted could transfer heat about 116 kW. And the drying capacity would increase from 1600 kg of dried product to about 4267,6 kg of dried product.